2019
DOI: 10.1002/jcp.29101
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic anti‐inflammatory pathway confers airway protection against oxidative damage and attenuates inflammation in an allergic asthma model

Abstract: Asthma is characterized by the influx of inflammatory cells, especially of eosinophils as well as reactive oxygen species (ROS) production, driven by the release of the T helper 2 (Th2)-cell-associated cytokines. The cholinergic anti-inflammatory pathway (CAP) inhibit cytokines production and controls inflammation. Thus, we investigated the effects of pharmacological activation of CAP by neostigmine on oxidative stress and airway inflammation in an allergic asthma model. After the OVA challenge, mice were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Anti-cholinergic therapy has been suggested to intensify eosinophil interactions with airway nerves in a model of asthma in guinea pigs (Verbout et al, 2009). In according to this idea, Antunes et al ( 2019) (Antunes et al, 2019) recently showed that the pharmacological Fig. 10.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-cholinergic therapy has been suggested to intensify eosinophil interactions with airway nerves in a model of asthma in guinea pigs (Verbout et al, 2009). In according to this idea, Antunes et al ( 2019) (Antunes et al, 2019) recently showed that the pharmacological Fig. 10.…”
Section: Discussionmentioning
confidence: 99%
“…A model of allergic asthma was used to study the neostigmine-induced activation of CAP and its effect on oxidative stress and airway inflammation. Activation of CAP with neostigmine reduced the levels of pro-inflammatory cytokines (IL-4, IL-5, IL-13, IL-1β, and TNF-α), which, in turn, reduced the inflow of eosinophils into the bronchial mucosa [ 52 ].…”
Section: Organ Dysfunction and Pathology Of The Ans In Sepsismentioning
confidence: 99%
“…To our surprise, a screen of the respective literature revealed that the precise role of the CS in the response to psychosocial stress is largely unknown and even less is known about a role for SLURP-1. Some information was even contradictory, suggestive of both, a protective and a harmful role of the CS in host defense and inflammatory disease (12,16,(23)(24)(25). This called for research that clarifies the role of SLURP-1 at the crossroads between pro-inflammatory and anti-inflammatory stress responses.…”
Section: Introductionmentioning
confidence: 99%